Hsp90‐mediated regulation of DYRK3 couples stress granule disassembly and growth via mTORC1 signaling. (19th March 2021) - Mediani, Laura; Antoniani, Francesco; Galli, Veronica; Vinet, Jonathan; Carrà, Arianna Dorotea; Bigi, Ilaria; Tripathy, Vadreenath; Tiago, Tatiana; Cimino, Marco; Leo, Giuseppina; Amen, Triana; Kaganovich, Daniel; et al.
Abstract: Stress granules (SGs) are dynamic condensates associated with protein misfolding diseases. They sequester stalled mRNAs and signaling factors, such as the mTORC1 subunit raptor, suggesting that SGs coordinate cell growth during and after stress. However, the molecular mechanisms linking SG dynamics and signaling remain undefined. We report that the chaperone Hsp90 is required for SG dissolution. Hsp90 binds and stabilizes the dual‐specificity tyrosine‐phosphorylation‐regulated kinase 3 (DYRK3) in the cytosol. Upon Hsp90 inhibition, DYRK3 dissociates from Hsp90 and becomes inactive. Inactive DYRK3 is subjected to two different fates: it either partitions into SGs, where it is protected from irreversible aggregation, or it is degraded. In the presence of Hsp90, DYRK3 is active and promotes SG disassembly, restoring mTORC1 signaling and translation. Thus, Hsp90 links stress adaptation and cell growth by regulating the activity of a key kinase involved in condensate disassembly and translation restoration. SYNOPSIS: Hsp90 promotes the disassembly of stress granules and other condensates in part by binding and stabilizing the dual‐specificity tyrosine‐phosphorylation‐regulated kinase 3 (DYRK3). Inhibition or loss of Hsp90 results in DYRK3 destabilization, stress granule persistence and failure to restore mTORC1 signaling and translation. Hsp90 regulates DYRK3 stability and activity. Partitioning into condensates protects DYRK3 from aggregation. Hsp90 couples SG disassembly and mTORC1‐dependent cell growth in part via DYRK3. ALS fibroblasts and motor neurons show reduced expression of DYRK3. Abstract : Hsp90 promotes the disassembly of stress granules and other condensates in part by binding and stabilizing DYRK3. Inhibition or loss of Hsp90 results in DYRK3 destabilization, stress granule persistence and failure to restore mTORC1 signaling and translation.